Strategi Inspektorat dalam Mengawal Pembangunan Infranstruktur Melalui Alokasi Dana - Wijaya, Dian; Elton; Yudha Utama, Jeny (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2022)
Village development which is composed as an effort to change social conditions, call it agents of change, internal problems / problemsthe Village government as in the supervision of the performance of the Village government by the Government's Internal Supervisory Apparatus, the main problem regardingHow is the Strategy of the Inspectorate in Overseeing Infrastructure Development through the Allocation of Village Funds in Umbunasi Village. Is there any goal toin this case to find out the Inspectorate's Strategy in Overseeing infrastructure development planning in carrying out budget preparationVillage Income and Expenditures that are consistent and in accordance with the budgeting rules of the Umbunasi Village community. There is any goal to be inthis is to find out the Inspectorate's Strategy in Overseeing infrastructure development planning in carrying out budget preparationVillage Income and Expenditures that are consistent and in accordance with the budgeting rules of the Umbunasi Village community. The concept of Good Governance according toSoepomo the term Good Governance is good government in carrying out tasks that are accountable to the professional public,Transparent, responsible. Miftha Thoha said that apart from the government components, the private sector, the people, were very decisive in creating governancegood governance is moral. This study uses a qualitative methodology where primary data collection such as observations, interviews,and documents, determine research sites, and analyze data and mechanisms to organize and organize them. Strategy ConclusionThe South Nias Mist Inspectorate failed to supervise development in Umbunasi Village, but the Umbunasi Village government carried outthe program works properly and correctly with P3MD escort